IT'S SPLITSVILLE SURVIVING YOUR DIVORCE - Gross, James J. (Apress : Imprint: Apress, 2013)
Thinking about divorce? Already in the process of divorce? You need this book. Divorce is complex, and complications are not what you need when you are facing its emotional and financial pressures. In It's Splitsville: Surviving Your Divorce, veteran divorce attorney James J. Gross breaks down the divorce process for nonlawyers in easy-to-understand steps. He explains the legal system in plain and simple language, and he describes the process of obtaining a fair separation agreement and navigating family law and the legal system. Just as important, it explains the emotional hazards of divorce and how to withstand the myriad pressures you will face. It's Splitsville: Surviving Your Divorce: Explains divorce laws in easy-to-understand words. Guides you through the steps for obtaining a separation agreement. Provides a friendly userỚ"s manual for divorce court. Helps you and your spouse decide whatỚ"s best for the children. Shows you how to protect your assets to the legal extent possible. Explains when and how to play hardball.℗ Nearly a million people get divorced each year in the United States. Many, if not most, could be handled far better for all parties involved.℗ It's Splitsville: Surviving Your Divorce will guide you safely through the hazards of divorce, show you how to understand and survive the complicated legal process,℗ explain underhanded tactics and how to combat them, and help emerge on the other side as a stronger, wiser, and better person.